The Flows of the Pacific: Asian Foreign Exchange Markets Through Tranquility and Turbulence - Dagfinn Rime; Hans Jørgen Tranvag (Norges Bank, 2012)
Using the longest data set on FX order flow to date, along with the broadest coverage of currencies to date, we examine the effect of FX order flow on exchange rates across small and large currencies, currencies with floating or fixed regimes, and across both tranquil and turbulent periods. Over our 15 years of data for eleven Asian and Australasian currencies, we find that order flow has a potentially strong impact on all exchange rates in the sample. The effect is strongest on floating exchange rates, both economically and statistically, but is sizeable also on the other exchange rates, especially during periods of turbulence. By creating a measure of regional order flow, we show that all exchange rates depreciate as flows are moved out of Asia/Australasia and into US dollars. This is true both across regimes and if their own flow is not included in the structure of the regional flow.
hdl:11250/2496837
Keywords: F31; G01; G15; 330; asian exchange rates; australasian exchange rates; order flow; microstructure; financial crisis